THE ANALYSIS STUDY OF OSTEOPOROSIS AND FRACTURE RISK : A TEN YEARS SYSTEMATIC REVIEW - Yulanda Putra, Yosie; Tri Lestari, Deby; Saputra, Zikri; Merisa Liona, Bella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Microarchitecture degeneration and reduced bone mass, which increase fragility and fracture susceptibility, are hallmarks of osteoporosis, a systemic skeletal disorder. Disease has a substantial effect on fracture healing as well as bone mass and microstructure. More accurate fracture risk assessment and a wider range of treatment choices are the results of research advances. Effective treatment regimens for osteoporosis have been aided by the fracture risk assessment tool (FRAX), which has had a substantial impact on clinical decision-making and intervention levels. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. A number of websites, including ScienceDirect, PubMed, and SagePub, were utilized to gather the literature. Result: The study looked at more than 4,000 publications using reputable sources including Science Direct, SagePub, and PubMed. After it was decided that eight publications needed greater investigation, a more extensive review of the entire literature was carried out. Conclusion: Studies have shown that osteoporosis can lead to fractures, with the Fracture Risk Assessment Tool (FRAX) and Bone Mineral Density (BMD) testing being used to assess fracture risk in women. Studies have shown that bone anabolic treatments can reduce fracture risk, but the certainty of these results is low due to the small number of studies.